Sound? It's Unique Band? Highlanders - Unknown (Panorama Supplement)
Forsyth Highlanders, the innovators, have tuner-arranger Bertie Marshall to thank for that title. Bertie Marshall first introduced the double tenor, then raised the pitch of the band, put amplified pans on the road and now has invented a double second with dampers. As the band strikes up, you know who is beating since the sound is unique and the style inimitable.
Keywords: Steel drum (Musical instrument) -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Inventors -- Trinidad and Tobago; Arrangers (Musicians) -- Trinidad and Tobago